Effectiveness of a comprehensive integrated module using interactive lectures and workshops in understanding and knowledge retention about infant feeding practice in fifth year medical students: a quasi-experimental study. Issue 1 (December 2016) - Sjarif, Damayanti; Yuliarti, Klara; Wahyuni, Luh; Wiguna, Tjhin; Prawitasari, Titis; Devaera, Yoga; Triyuniati, Henni; Afriansyah, Andika
Abstract Background Sixty percent of the 10.9 million under-5 deaths every year are related to malnutrition. More than two thirds of malnutrition is caused by inappropriate infant feeding practice. Only 35 % of mothers worldwide provide 4 months of exclusive breast-feeding, while complementary feeding is often untimely, nutritionally inadequate, hygienically poor, and improperly delivered. The existing pediatric nutrition module in our institution does not include proper delivery of food that involves oral–motor skills and feeding behavior. To scale up the knowledge and skill of medical students regarding evidence-based infant feeding practice, we designed a new module composed of comprehensive and integrated lectures with additional multidisciplinary lectures on oral–motor skill development and feeding behavior. Methods A quasi-experimental study was conducted to evaluate the efficacy of the new module compared to the previous module. Fifth year medical students of Universitas Indonesia were divided into intervention and control groups. The control group received lectures and a paper-based workshop. The intervention group received comprehensive and integrated interactive lectures with additional multidisciplinary lectures on oral–motor skill development and behavioral approaches to feeding problems. A hands-on workshop using real cases shown on recorded video and role-play sessions was also presented to the intervention group. A pre-/post-test, 3-month retention test, and Observed Structured Clinical Examination (OSCE) were performed to evaluate understanding, knowledge retention, and counseling skills. Results A linear mixed effect model with a random intercept analysis for pre-test, post-test, and retention test scores showed significant higher result for intervention group compared to control group (p  < 0.001). Comprehensive knowledge and counselling skills were better in the intervention group than in the control group as shown by the OSCE score (68.6 vs 59.3, p  < 0.001). Conclusions Our comprehensive integrated infant feeding practice module, which incorporates multidisciplinary learning processes and an interactive hands-on workshop with a role-play session yields better knowledge understanding and counseling skills compared with the existing module. Comprehensive knowledge and good counseling skills of medical students as future doctors are a pre-requisite to provide effective education to parents to support successful infant feeding practices.